TATA LETAK, KONSTRUKSI DAN PERMASALAHAN KANDANG AYAM PETELUR - Syahruddin Syahruddin; Nibras Karnain Laya; Syukri I Gubali; Fahria Datau; Suparmin Fathan; Safriyanto Dako (Jambura Journal of Husbandry and Agriculture Community Serve (JJHCS), 2022)
High egg production is not only determined by animal feed and drinking, but the cage is also an important factor, because cages that do not meet the requirements will have an impact on livestock, farmers and the community. Community service activities aim to increase knowledge and skills for employees and cage workers at Bintang RS. Pulubala about good cage management for laying hens. In efficient cage construction and layout at Bintang RS. Pulubala can cause a decrease in egg production and the health of chickens. The layout, construction of cages and equipment of existing cages at Bintang RS. Pulubala has not met the requirements for non efficient and productive laying hens. So that egg production and the health of chickens have not been maximized. It can be concluded that the extension activities on productive and efficient housing management can be implemented in Bintang RS. Pulubala. Keywords: laying hens; cage construction; layout